P-736 Twins, an instant family: beyond the risks and health in Central America. (30th June 2022) - Lucero, A.I; Mejia, F; Colon, A
Abstract: Study question: Why do patients attending fertility centers in Centralamerica consider twins as the best possible outcome? Summary answer: In Centralamerica patients expect to have twins after a fertility treatment. Preliminary results show that, from a specialist's perspective, this expectation might be financially driven. What is known already: Twins have fascinated humanity since early times. Every culture in the world has a different reaction to the birth of twins and has myths about them. Some myths are still present in current times and affect our decisions. After a fertility treatment, the likelihood of having twins increases, which has contributed to a worldwide increase of the twin birth rate. In spite of the risks, some patients prefer to have twins.  Study design, size, duration: This is a qualitative study based on anthropological theory and ethnographic research. Semi-structured interviews were conducted to infertility specialists during July of 2020 in Centralamerica. These six countries are a cultural region that shares historical and economic features which enables a socio-cultural anthropological research. The framework for the interview's structure is the ecological paradigm from medical anthropology theory. In this paradigm the individual is seen as part of a context that influences their medical decisions. Participants/materials, setting, methods: The participants were infertility specialist who had more than 3 years of experience and practice reproductive medicine in Central America. The method was a semi-structured interview via Zoom and was recorded and then transcribed with the software Transcriptions Version 1.2. The results were coded and analyzed with cognitive anthropology methods to identify cultural models in the speech. In ethical aspects, the confidentiality of the interviewee was considered important and was protected through informed consent. Main results and the role of chance: The results of the interviews with infertility specialists indicate that they have difficulties explaining patients about the risks and complications of a multiple pregnancy. According to the physicians, many patients expect twins after a treatment. The patients have the idea that they will have "two for one" ( "dos de un solo") and believe that the raising of two babies will require less time and money. The birth of twins is considered a "double blessing" ( "doble bendicion" ) or a "double price" ( "doble premio" ). With one single treatment they hope to get the "ideal family" that consist of one girl and one boy ( "tener la parejita" ). The patients have preconceived ideas that are influenced by their environment, like family members, friends and the media. Central America was part of the mesoamerican region were maya and aztecs myths continue to influence the popular culture and people continued to believe that twins have special connections and could have a good sibling relationship. Physicians are not aware that the media and family have so much weight in the medical decisions of their patients only focus on the fact that patients underestimate the risks. Limitations, reasons for caution: The reason for caution is that this is a local study that cannot be generalized in time and place. Wider implications of the findings: The results would help to design interviews for patients with the final purpose of understanding their perceptions and attitudes toward twins. In a region with no public health policies regarding infertility treatments, the results can improve communication between the doctors and patients to reduce twin rates. Trial registration number: (')